Pengaruh Build Up Angle Untuk Kestabilan Formasi Pada Proses Cabut Rangkaian BHA - Abdullah Rizky Agusman; Eko Prastio; Muhammad Alfarizi (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
Directional drilling is a method for directing a drilled well along a predetermined path to reach the target. Vertical wells are usually defined as wells with a slope below 5°. Wells with a slope of more than 60° are also called directional wells.Directional drilling is only carried out for certain reasons and circumstances. The reasons for carrying out directional drilling are geographical reasons, geological reasons, and other reasons related to productivity issues.In this thesis the author tries to determine the KOP, azimuth, inclination and EOB points so that the process of extracting the BHA series can run smoothly without having to experience formation collapse or the BHA series being pinched in the formation in the MAR-1 well, followed by comparing the actual data.